PEMBELAJARAN KOOPERATIF TEAM GAMES TOURNAMENT DAN LEARNING CYCLE PADA MATA PELAJARAN ELEKTRONIKA - Depari, Ganti (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
This study discusses the comparison of the effectiveness of Team games tournament cooperative learning model and learning cycle model on students’ achievement. Both of these methods emphasize a situation where students work in small groups and help each other to learn the course material. Students become the center of the learning activity (student-centered). This study uses quasi-experiment method, with subjects consisting of two classes, i.e. class X TAV 3 and X TAV 4. The results show that there is a difference in average academic achievement between learning cycle model (0,58) and team games tournament (0,73). tobt = 3,69, thus tobt = 3,69 ttable(0.95)(58) = 1,676. It is concluded that a learning activity with TGT cooperative learning model is better than a learning activity with learning cycle model in improving students’ achievement.